Hematological Effects of Vigna unguiculata subsp. cylindrica in Anemic Mice: An Experimental Study - Norsiah, Wahdah; Thuraidah, Anny; Herlina, Tini Elyn (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Anemia is a global health problem that impairs cognitive function, physical performance, and maternal–child health. This study aimed to evaluate the hematological effects of Vigna unguiculata subsp. cylindrica (Nagara Bean) as a potential functional food in sodium nitrite (NaNO₂)-induced anemic mice. Thirty-three male BALB/c mice (8–12 weeks, 25–30 g) were randomly assigned into six groups: normal control (K), negative control (K−, anemia-induced), positive control (K+, iron-supplemented), and three treatment groups (P1, P2, P3) that received Nagara Bean-based feed for 1, 2, and 3 weeks, respectively. Hemoglobin (Hb), hematocrit (Hct), and red blood cell (RBC) levels were measured using Point-of-Care Testing (POCT) and manual cell counting. The results showed increases in Hb, Hct, and RBC across the treatment groups; however, statistical analysis indicated that these improvements were primarily associated with the duration of feed administration rather than treatment type. The greatest hematological improvement was observed after two weeks of feeding (P2). These findings indicate that Nagara Bean supplementation supports hematological recovery in anemic mice. The results suggest that Vigna unguiculata subsp. cylindrica has potential as a natural, affordable, and locally available source of bioavailable iron for anemia prevention and dietary intervention programs.